EFFICACY OF AZITHROMYCIN AND ITS IMPACT IN CYTOKINE SYSTEM IN UROGENITAL INFECTIONS - A. A. Khryanin; O. V. Reshetnikov; I. D. Safronov; A. N. Trunov; N. B. Kulikova (Антибиотики и Химиотерапия)
Seventy five patients with urogenital chlamydial and mycoplasmic infections were enrolled in the trial. In the etiotropic therapy azithromycin was used in the standard dosage (1.0-1.5 g) depending on the infection. The treatment with azithromycin, in addition to the high eradication rates, was also evident of its effect on the cytokine levels in the patients, that was characteristic of a significant increase of the IFN-γ level and a decrease of the IL-β and IL-6 levels in the blood.